Creative approaches to community cohesion. (1st September 2002) - Vincent, Robert; Coles, Maurice
This article is an updated version of the talk that Robert Vincent and Maurice Coles from Leicester City's School Development Support Agency (SDSA) presented to the ALAOME Conference in March 2003. It aims to detail the background and underlying principles of Community Cohesion and some of the funding streams that support it. It outlines the story of Leicester City LEA's decision to locate some of its NRF funding to support its Education Development Plan (EDP) Priority 8, 'Literacy in Development Groups' and details some of the processes and projects that were the outcomes of this decision. It ends with some general learning points that may be of help to Local Authorities generally and LEAs in particular.